Corrompidos pelo interesse : os diamantes do Brasil e o controle da corrupção (Distrito Diamantino, 1729-1821) - Régis Clemente Quintão (2022)
This thesis deals with corruption as a problem that mobilized the agents responsible for the administration of diamonds on both sides of the Atlantic, between 1729 and 1821. The option for the long time span is justified by the purpose of studying the continuities and transformations of the concept of corruption and practices to combat it. Considering the symbolic and economic importance of diamonds for the Portuguese monarchy in the 18th century, the main objective is to analyze the speeches and actions of the Portuguese authorities and those established in the Diamantino District that aimed to contain illegalities and unwanted conduct in the exercise of the management positions in the diamond administration. The central hypothesis points out that there was an effort to curb the behavior that caused damage to the Real Fazenda (Royal Treasury) and that resulted in corruption, which was sought to be avoided. The researched sources, in part unpublished, belong to several Portuguese and Brazilian institutions. From them, how corruption was seen by the Portuguese Crown is investigated, the values and principles that articulated this concept and the contemporary language to refer to corruption and illicit practices. The documents were interpreted in the light of the thriving and recent historiography of corruption, with emphasis on Spanish, Dutch and Brazilian productions, which not only discuss the applicability of the concept, but also the existence of mechanisms to combat corruption in the Modern Time. The research does not focus on case studies, although this methodological approach is present in the thesis. The privileged resource resides in the evaluation of the administrative changes or reforms which marked the mining of diamonds throughout the different systems, such as capitation (1730-1734), contracts (1740-1771) and the royal monopoly (1772-1845), in order to observe possible changes in ideas and limits on accepted conduct and those considered criminal. In dialogue with the historiography and by examining the selected documents, it was found that the word corruption was commonly used not only in its moral sense, but also as a result of the misconduct of royal officials. Therefore, the fight against corruption was at the origin of the changes in the referred administrative systems. The authorities endeavored to prevent the main illicit acts, such as smuggling, account fraud, theft from Real Fazenda, favoritism of relatives and friends and malfeasance. In addition, technical and professional standards were disseminated for the performance of royal officials, punishing what was considered abuse and that caused damage to the Real Fazenda. However, this control was often subject to the interests and disputes of diverse groups, including officials, local residents, foreigners and the Portuguese Crown itself, indicating some limits of actions in the fight against corruption in the Diamantino District.